POLA ASUH KEPERAWATAN DALAM TINJUAN SOSIOLOGI (Studi Kasus: Perawat di Ruang Rawat Inap RSJ. Hb. Sa’anin Padang) - Erningsih Erningsih (Universitas Islam Negeri Imam Bonjol Padang, 2013)
Prior to the establishment of special hospitals for psychiatric problems of people with mental disorders aretreated and handled by the family. Reality found there are still people with mental disorders are deprived anddiscriminated against in social life such patients have undergone unhumanistic treatments. In this relation,sending the patients to psyciatric hospitals may be considered to be a humanistic solution that may becomeimportant in helping such mentally disturbed patients especially to help them return to their normal life. For thatreason, this study focused on social aspects associated with some nursing pattern in psyciatric hospital (sociologicalperspektive). The results indentified that interactions between patients and nurses could be categorized into 3patterns as which 1) the patients needs, 2) time and 3) accomodation or facilities have been focused.